A review study on seismic behavior of individual and adjacent structures considering the soil – Structure interaction. (June 2023) - Abdulaziz, Mohammed A.; Hamood, Mohammed J.; Fattah, Mohammed Y.
Abstract: Researchers and engineers have shown a keen interest in the impact of soil-structure interaction (SSI) on seismic response of structures throughout the past three decades. Less research has been done on the experimental investigation, with the majority of these studies concentrating on theoretical analysis. When the structure, foundation, and soil medium work together, the actual behavior of the structure is significantly different from what would be expected if only the structure were taken into account. The building frames' overall stiffness is reduced by the flexible earth medium beneath the foundation, increasing the system's natural period. The term "soil-structure interaction" refers to a group of processes that affect both the responsiveness of soils to the presence of structures and the response of structures to the flexibility of their foundation soils. The combined structure-foundation-soil system is often ignored by analytical and numerical methods for dynamic analysis. It has been acknowledged that SSI impacts could have a big effect, especially when larger constructions and soft soil are involved. In this work, investigations on the interactions between neighboring structures' soil properties are reviewed. These studies are divided into two groups: theoretical/numerical studies of SSI and experimental studies of SSI. It was determined that taking into account various factors, including soil structure interaction, soil type, building stiffness, infill wall stiffness, wall location, distance between adjacent buildings, and building height, significantly affected the displacement of the building frame's base and its time course. The significance of taking the underlying soil into account decreases as the soil stiffness rises.